Influence of different quenching media on thermal properties, microhardness and microstructure of Ti-Ni-Zr shape memory alloy - Mohammed, Safar Saeed; Dagdelen, Fethi; Qadir, Rezhaw Abdalla; Kok, Mediha; Balci, Esra; Rasul, Hawzhin Hamad; Omer, Lina Swara (Springer, 2026)
This study examines the impact of different quenching media water, liquid nitrogen, and alcohol on the structural and physical properties of Ti-Ni-Zr shape memory alloys (SMAs) heat-treated at 800 degrees C for one hour. Differential Scanning Calorimetry (DSC) confirmed martensitic phase retention at room temperature for all samples. Transformation temperatures increased after heat treatment, except for austenite start (As\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${A}_{ ext{s}}$$\end{document}) and martensite finish (Mf\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${M}_{ ext{f}}$$\end{document}) in water-quenched samples, indicating stress from rapid cooling. Alcohol quenching resulted in the smallest temperature hysteresis due to reduced internal stress. Thermodynamic analysis showed enhanced phase stability with alcohol and liquid nitrogen quenching through lower enthalpy and entropy changes during heating and higher values during cooling. Gibbs free energy calculations indicated superior thermodynamic efficiency for these media compared to water. Microhardness tests revealed that liquid nitrogen-quenched samples had the highest hardness due to refined microstructures, while alcohol-quenched samples showed the lowest due to retained austenite. X-ray diffraction (XRD) analysis confirmed maximum martensite content with minimal secondary phases for liquid nitrogen quenching, while alcohol quenching promoted austenite retention and Ti2Ni precipitation. Grain size analysis highlighted finer grains from faster cooling, though thermal history played a key role. These findings underscore the importance of quenching media selection in tailoring Ti-Ni-Zr SMA properties for advanced applications.
Keywords: Ti-Ni-Zr Shape Memory Alloy; Quenching Medium; Ltsma; Heat Treatment; Liquid Nitrogen; Enthalpy; Entropy